2017
DOI: 10.1088/1367-2630/aa8fdd
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in ${\mathscr{P}}{\mathscr{T}}$-symmetric ladders of optical waveguides

Abstract: We consider a  -symmetric ladder-shaped optical array consisting of a chain of waveguides with gain coupled to a parallel chain of waveguides with loss. All waveguides have the focusing Kerr nonlinearity. The array supports two co-existing solitons, an in-phase and an antiphase one, and each of these can be centred either on a lattice site or midway between two neighbouring sites. We show that both bond-centred (i.e. intersite) solitons are unstable regardless of their amplitudes and parameters of the chain.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 92 publications
1
14
0
Order By: Relevance
“…It can be checked that, as well as it is obvious in Eqs. (37) and (38), the N (σ, k) dependence corresponding to the defocusing nonlinearity satisfies the above-mentioned anti-VK criterion, ∂N/∂k < 0 [79], at all values of σ. Accordingly, all the pinned modes are stable, both at γ = 0 and γ > 0, similar to the case of the self-defocusing cubic nonlinearity [63].…”
Section: Exact Solutions With the Self-defocusing Nonlinearitymentioning
confidence: 82%
“…It can be checked that, as well as it is obvious in Eqs. (37) and (38), the N (σ, k) dependence corresponding to the defocusing nonlinearity satisfies the above-mentioned anti-VK criterion, ∂N/∂k < 0 [79], at all values of σ. Accordingly, all the pinned modes are stable, both at γ = 0 and γ > 0, similar to the case of the self-defocusing cubic nonlinearity [63].…”
Section: Exact Solutions With the Self-defocusing Nonlinearitymentioning
confidence: 82%
“…For this reason, antisymmetric solitons are not considered in detail below below (they may be made stable in a discrete version of Eqs. (2) [59]). As mentioned above, an essential difference of the PT -symmetric system (2) from its conservative counterpart, with γ 0 = 0, is that, at A 2 > A 2 crit , unstable PT -symmetric solitons are not replaced by stable asymmetric ones (cf.…”
Section: The Modelmentioning
confidence: 99%
“…The PT symmetry in an optical waveguide (as well as its CP counterpart) may naturally combine with the material Kerr nonlinearity, giving rise to propagation models based on cubic nonlinear Schrödinger equations (NLSEs) with the complex potentials subject to condition (1). These models may generate PT -symmetric solitons, which were addressed in many theoretical works [18], [23]- [59], [15] (see also reviews [41,42]), and experimentally demonstrated too [34]. Although the presence of the gain and loss makes PT -symmetric media dissipative, solitons exist in them in continuous families, similar to the commonly known situation in conservative models [43], while usual dissipative solitons exist as isolated solutions (attractors, if they are stable) [44].…”
Section: Introductionmentioning
confidence: 99%
“…The eigenvalues are symmetric relative to the imaginary axis. To be precise, if λ 0 is an eigenvalue with the eigenvector v 0 = (a, b) T , then −λ 0 is another eigenvalue with the eigenvector σ 3v0 = (a, −b) T by the Hamiltonian symmetry σ 3 L =Lσ 3 .…”
Section: Krein Signature For the Nls Equationmentioning
confidence: 99%
“…The linear Schrödinger equation with a complex-valued PT -symmetric potential was considered in [35], where the indefinite PT -inner product with the induced PT -Krein signature was introduced in the exact correspondence with the Krein signature for the Hamiltonian spectral problem (1.9). Coupled non-Hamiltonian PT -symmetric systems with constant coefficients were considered in [2,3] (see also [48]), where the linearized problem was block-diagonalized to the form for which the Krein signature of eigenvalues can be introduced. A Hamiltonian version of the PT -symmetric system of coupled oscillators was considered in [11,12], where the Krein signature of eigenvalues was introduced by using the corresponding Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%